2016
DOI: 10.1016/j.apcata.2016.05.019
|View full text |Cite
|
Sign up to set email alerts
|

One-pot two-step process for direct propylene oxide production catalyzed by bi-functional Pd(Au)@TS-1 materials

Abstract: Different bi-functional materials (Pd(Au)@TS-1) based on metallic nanoparticles supported onto active nanocrystalline titanium silicalite (TS-1) zeolites were synthesized, characterized and used as recyclable heterogeneous catalysts for direct propylene oxide production from hydrogen, oxygen and propylene through one-pot two-step consecutive process. These catalysts allowed carrying out the combined reaction where metallic nanoparticles catalyzed the formation of in situ H 2 O 2 that was the necessary intermed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…31 The suggested mechanisms for epoxidation here involve hydrogen peroxide or hydroperoxyl species that are generated and used in situ, with the nanoparticles supported on a material with epoxidation catalysing sites such as anatase TiO2, or porous titania containing materials like TS-1. 32,33 We have also shown that nanoparticles of AuPd alloys are active catalysts for the oxidation of methane to partial oxidation products, particularly methanol. Initially, using nanoparticles supported on titania, 34,35 it appeared that this reaction required the use of hydrogen peroxide as oxidant, and since the current market price of hydrogen peroxide is greater than methanol this imposes unacceptable costs on the process.…”
Section: Introductionmentioning
confidence: 88%
“…31 The suggested mechanisms for epoxidation here involve hydrogen peroxide or hydroperoxyl species that are generated and used in situ, with the nanoparticles supported on a material with epoxidation catalysing sites such as anatase TiO2, or porous titania containing materials like TS-1. 32,33 We have also shown that nanoparticles of AuPd alloys are active catalysts for the oxidation of methane to partial oxidation products, particularly methanol. Initially, using nanoparticles supported on titania, 34,35 it appeared that this reaction required the use of hydrogen peroxide as oxidant, and since the current market price of hydrogen peroxide is greater than methanol this imposes unacceptable costs on the process.…”
Section: Introductionmentioning
confidence: 88%
“…In particular the catalytic conversion of propylene to propylene oxide is a pertinent example of a major industrial process that utilises TS‐1, with over 1.2 Mt of propylene oxide produced annually, and the vast majority utilised in the production of polyurethane via the HPPO process. Furthermore, a growing interest has been placed on Au, and Au‐Pd, nanoparticles supported on TS‐1 for the in situ generation of H 2 O 2 for a variety of selective oxidation reactions. We have previously investigated the role of zeolites such as TS‐1, HZSM‐5 and zeolite‐Y as supports for precious metals in the direct synthesis of H 2 O 2 , as well as CO oxidation, with H 2 O 2 productivities for the zeolite supported catalysts much greater than the analogous catalysts supported on common oxide supports including TiO 2 , Al 2 O 3 and SiO 2 likley due to their strong acid characters.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the most straightforward production process for propylene oxide synthesis, which is the direct oxidation of propylene with O 2 , the major hurdles to obtain a highly pure monomer under safe and high yielding processes have precluded major industrial applications. Díaz, Corma et al reported an elegant one-pot two-step process for direct propylene oxide production from propylene, H 2 , and O 2 catalyzed by a bifunctional material (Pd(Au)@TS-1) based on metallic NPs supported on nanocrystalline titanium silicalite (TS-1) zeolites [122]. The resulting metallic nanoparticles encompassed the in situ formation of H 2 O 2 in a controlled fashion, which triggered propylene epoxidation catalyzed by the TS-1 nanocrystalline matrix support, working under safe supercritical CO 2 conditions.…”
Section: Applications In Catalysis Of Bmnps In Supercritical Fluidsmentioning
confidence: 99%
“…The resulting metallic nanoparticles encompassed the in situ formation of H 2 O 2 in a controlled fashion, which triggered propylene epoxidation catalyzed by the TS-1 nanocrystalline matrix support, working under safe supercritical CO 2 conditions. These bifunctional catalysts showed high reusability and stability demonstrated through several catalytic cycles, yielding a more sustainable process for future industrial applications [122]. For a summary of BMNPs in supercritical fluids applied in catalysis, see Table 4 at the end of this section.…”
Section: Applications In Catalysis Of Bmnps In Supercritical Fluidsmentioning
confidence: 99%